The Role of Islamic Educational Management in Promoting Inclusive and Equitable Quality Education - Hadi, Samsul; Santosa, Tomi Apra; Wantu, Hasyim Mahmud (Penerbit Widina, Widina Media Utama, 2025)
This study explores the pivotal role of Islamic Educational Management in fostering inclusive and equitable quality education in accordance with the objectives of Sustainable Development Goal 4. Grounded in the principles of Islamic values such as justice (‘adl), compassion (rahmah), and equality (musawah) Islamic educational institutions are uniquely positioned to address disparities in access and learning outcomes. Using a qualitative approach, this research analyzes various management strategies employed by Islamic schools and madrasahs in promoting educational inclusivity, especially among marginalized and underserved communities. The findings indicate that effective leadership, community engagement, and curriculum integration of Islamic ethical values significantly contribute to creating a more inclusive and equitable educational environment. Furthermore, the study highlights the importance of policy alignment between national education standards and Islamic educational objectives. This research underscores the need for a transformative management model that harmonizes faith-based values with contemporary educational demands to ensure that no learner is left behind.ABSTRAKPenelitian ini mengeksplorasi peran penting Manajemen Pendidikan Islam dalam membina pendidikan berkualitas yang inklusif dan adil sesuai dengan Tujuan Pembangunan Berkelanjutan 4. Berdasarkan prinsip-prinsip nilai-nilai Islam seperti keadilan (‘adl), kasih sayang (rahmah), dan kesetaraan (musawah) lembaga pendidikan Islam diposisikan secara unik untuk mengatasi kesenjangan dalam akses dan hasil pembelajaran. Dengan menggunakan pendekatan kualitatif, penelitian ini menganalisis berbagai strategi manajemen yang digunakan oleh sekolah dan madrasah Islam dalam mempromosikan inklusivitas pendidikan, terutama di kalangan masyarakat yang terpinggirkan dan kurang terlayani. Temuan-temuan menunjukkan bahwa kepemimpinan yang efektif, keterlibatan masyarakat, dan integrasi kurikulum nilai-nilai etika Islam secara signifikan berkontribusi untuk menciptakan lingkungan pendidikan yang lebih inklusif dan adil. Lebih jauh, studi ini menyoroti pentingnya penyelarasan kebijakan antara standar pendidikan nasional dan tujuan pendidikan Islam. Penelitian ini menggarisbawahi perlunya model manajemen transformatif yang menyelaraskan nilai-nilai berbasis agama dengan tuntutan pendidikan kontemporer untuk memastikan bahwa tidak ada pelajar yang tertinggal.